Yellow-y Functions in Egg Melanization and Chorion Morphology of the Asian Tiger Mosquito, Aedes albopictus - Noh, Mi Young; Mun, Seulgi; Kramer, Karl J.; Muthukrishnan, Subbaratnam; Arakane, Yasuyuki (Frontiers in Cell and Developmental Biology, 2021)
The Asian tiger mosquito, Aedes albopictus, is one of the most serious public health pests, which can transmit various vector-borne diseases. Eggs from this mosquito species become dark black shortly after oviposition and exhibit high desiccation resistance. Some of the Yellow proteins that act as dopachrome conversion enzymes (DCEs) are involved in the tyrosine-mediated tanning (pigmentation and sclerotization) metabolic pathway that significantly accelerates melanization reactions in insects. In this research, we analyzed the function of one of the yellow genes, yellow-y (AalY-y), in eggshell/chorion melanization of Ae. albopictus eggs. Developmental and tissue-specific expression measured by real-time PCR showed that AalY-y transcripts were detected at all stages of development analyzed, with significantly higher levels in the ovaries from blood-fed adult females. Injection of double-stranded RNA for AalY-y (dsAalY-y) had no significant effect on fecundity. However, unlike dsEGFP-treated control eggs that become black by 2-3 h after oviposition (HAO), dsAalY-y eggs were yellow-brown at 2 HAO, and reddish-brown even at 48 HAO. dsEGFP eggs exhibited resistance to desiccation at 48 HAO, whereas approximately 50% of the dsAalY-y eggs collapsed when they were moved to a low humidity condition. In addition, TEM analysis revealed an abnormal morphology and ultrastructure of the outer-endochorion in the dsAalY-y eggs. These results support the hypothesis that AalY-y is involved in the tyrosine-induced melanin biosynthetic pathway, plays an important role in black melanization of the chorion and functions in conferring proper morphology of the outer-endochorion, a structure that is presumably required for egg desiccation resistance in Ae. albopictus.